Development of an innovation ecosystem model in handling the covid-19 in Indonesia - Handayani, Isyalia Dwi; Ikhwan, Hakimul; Pangaribowo, Evita Hanie (Jurnal Teknosains, 2024)
Technological innovation in the medical area is vital when the COVID-19 pandemic strikes, including in Indonesia. One of the essential innovations is a health facility for infection testing. Through the TFRIC-19 program, several Indonesian researchers have developed a mobile laboratory named Mobile Lab Biosafety Level 2 (MBSL2). MBSL2 is one of the medical innovations from the TFRIC-19 program as a measure to handle the COVID-19 pandemic in Indonesia. TFRIC-19 is an innovation system initiated by government institutions in the RnD area. Establishing TFRIC-19 was the initial step in handling the COVID-19 pandemic in Indonesia. This research aims to identify the actor's role in developing MBSL2. The technique uses the Ecosystem Pie Model (EPM) approach for analysis. It was found that the most essential aspect of creating innovation is collaboration between involved actors.